In-situ TEM observation of the ITB evolution in aluminum deformation twinning. (September 2022) - Yan, Kang; Chen, Zhongwei; Zhao, Yanni; Le, Wei; Xue, Yanqing; Naseem, Sufyan; Wafaa, Ali
Abstract: Deformation twinning is another important phenomenon besides dislocation slip during the plastic deformation of metals and alloys. In this work, the plastic deformation behavior of coarse-grained aluminum with high stacking fault energy was studied by in-situ tensile TEM. The results show that deformation twins appear at the crack tip under continuous applied stress, and the thickness of deformation twin increases with the appearance of incoherent twin boundaries (ITBs). Further analysis shows that Frank partial dislocation in deformation twins is decomposed into perfect dislocation and Shockley partial dislocation under the action of applied stress. These perfect dislocation and Shockley partial dislocation can slip along the crystal planes and react to form the dislocation combinations that constitute the ITB. The results of this work provide a new way for researchers to understand the role of ITBs on deformation twins and the formation of dislocation combinations in ITBs. Graphical abstract: Image, graphical abstract